HLA-Mediated Platelet Refractoriness: An ACLPS Critical Review. Issue 4 (3rd October 2018) - Schmidt, Amy E; Refaai, Majed A; Coppage, Myra
Abstract: Objectives: To provide an overview of the complexities associated with the human leukocyte antigen (HLA)-mediated platelet refractoriness. HLA antibody detection technologies and limitations associated with methodologies are discussed. Methods: A case scenario and review of relevant literature describing platelet refractoriness are presented, followed by a discussion of HLA antibody testing. Results: Following diagnosis of HLA-mediated refractoriness, a decision is made regarding the approach to obtain the appropriate platelets. The panel reactive antibodies (PRA) % of the patient, HLA typing, and limitations of the HLA testing should be taken into account when deciding which type of product would be the best option for a given patient. Conclusions: Following confirmation and review of HLA antibody testing, platelets are ordered based upon the PRA% and approach employed, HLA-matched platelets, antigen restricted platelets, or cross-matched platelets. The platelets are transfused and a posttransfusion increment count is monitored to determine transfusion success.